'As nearly subservient' as it could be? Vocationalism and senatorial speaking behaviour in the Irish Senate 1938–45. (2nd July 2016) - O'Donoghue, Martin
SUMMARY: Previous studies of the Irish Senate (Seanad Éireann) have derided its vocational ethos by pointing to the flaws in its electoral system and lack of government commitment to vocationalism. This article examines the reality of vocational representation in the House in its earliest years (1938–45) by analysing the motions raised by senators. Examined under different subject headings commensurate with the House's vocational panels, the motions indicate that although the electoral processes were blurred and unsatisfactory, speeches made by senators still often reflected vocational concerns. Even as party political concerns dominated, vocationalism was still seen to influence the speaking behaviour of some senators with Agricultural and Labour panellists displaying the strongest commitment to the principle. The motions also illustrate how the Seanad, shorn of the powers of its predecessor, assumed the role of a public forum for debate. Senators often felt that they fulfilled a purpose by simply raising matters of importance in the House, thus accounting for the large number of motions withdrawn after lengthy debates. This was especially true of the numerous motions raised by senators on matters relating to the Second World War. It is contended that such motions along with the domination of political parties and the persistent rumours of corruption in the electoral system served to undermine the vocational identity of the Seanad. However, despite these difficulties, the examples in early Seanad debates of some senators adhering to vocational ideals serve to highlight greater complexity in senatorial behaviour than dismissals of the Seanad often allow.